Knowledge based requirements specification for reconfigurable assembly systems - Hirani, Hitendra J. (2005)
Automated assembly technology may be the key to sustaining manufacturing industry in more developed countries. Currently this comprises dedicated systems that can assemble single products at high volumes and flexible systems to assemble a wide variety of products in low volumes. However, competitive forces demand a compromise between the two and Reconfigurable Assembly Systems are an avenue for achieving high volume and high variety production.